Degree and Rate of Growth Discordance in Dichorionic Twins Conceived by In Vitro Fertilization - Amira S. Egic; Donka V. Mojovic; Zagorka M. Milovanovic; Aleksandar B. Jurisic; Ljubomir P. Srbinovic; Suzana P. Krsmanovic; Natasa T. Karadzov-Orlic (Obstetrics and Gynecology International, 2014)
Objective. Our objective was to estimate degree and rate of discordant growth and its impact on perinatal outcome in dichorionic twin pregnancies conceived by in vitro fertilization (IVF) compared to those conceived spontaneously. Study Design. Growth discordance was defined as 90th percentiles for the study population. Adverse perinatal outcome was defined as 5-minute Apgar score <7 and/or admission to neonatal intensive care unit. Results. In the total study population of dichorionic twins (176 conceived by IVF and 215 spontaneously), 30% discordant growth represented the 90th percentile. After adjusting for gestational age, discordant twins conceived by IVF or spontaneously were at higher risk for adverse perinatal outcome (hazard ratio 4.4; 95% CI 2.4–8.3, P<0.0001; hazard ratio 2.5; 95% CI 1.5–4.4, P=0.001, resp.). Similar rates of 5-minute Apgar score <7, admission to neonatal intensive care unit, and delivery <34 weeks were found between discordant twins conceived by IVF and those conceived spontaneously. Conclusion. Dichorionic twins conceived by IVF are at similar risk for the rate and degree of discordant growth and adverse perinatal outcome compared to dichorionic twins conceived spontaneously.